Model Pembelajaran Steam dengan Media Loose Parts untuk Anak Usia Dini - Al Mubarok, Ahmad Aly Syukron Aziz (Amaliyatu Tadris, 2022)
Learning problems in producing creative students are still very limited, especially in PAUD. The problem can be seen from the achievement of children's development when the learning process takes place, children still have low communication skills and express opinions from the results of groups or collaborations that are still low. The factors that lead to none other than the still dominant role of teachers in learning and limiting children's creativity by providing less varied learning media because it uses the activity sheet available at school only. Selection of STEAM-based learning models (Science, Technology, Engineering, Art, Mathematics, by using loose parts media was chosen on the grounds that it is in harmony with 21st century education where critical thinking, creative, cooperative and communication skills are honed by playing.